1999
DOI: 10.4148/1090-7025.1014
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Phytoremediation of Methyl-tert-butyl Ether (MTBE) in Groundwater

Abstract: The feasibility of phytoremediation of groundwater contamination with methyl-tert-butyl ether (MTBE) was examined experimentally using a six-channel soil system with or without plants. Two bacterial strains capable of degrading MTBE were each added to two out of six channels. A solution of 0.84 mM MTBE was continuously fed into each channel at 1 L/day until a stable MTBE concentration level in the groundwater was established; then the feeding was switched back to distilled water. The channel groundwater efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Zhang et al [33] used a six-channel system with alfalfa plants and found pronounced rhizosphere effects. Two bacterial strains capable of degrading MTBE were added to two channels.…”
Section: Additional Findingsmentioning
confidence: 99%
“…Zhang et al [33] used a six-channel system with alfalfa plants and found pronounced rhizosphere effects. Two bacterial strains capable of degrading MTBE were added to two channels.…”
Section: Additional Findingsmentioning
confidence: 99%
“…4,11 The investigations contributed to transferral of the CW approach from small scale to field scale application. 12,13 Few studies have considered the flux of VOCs into the atmosphere for mass balancing based on experimental data 7,14 or simulations. 15 Recent wetland research also attempted to examine the role of plant uptake during VOC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…10) by changing the water velocity (v z ) through transpiration. Studies report that transpiration contributes significantly to the transport of organic contaminants in soil [136,137].As plants take up water from the subsurface, the horizontal water recharge can lead to an increase in the advective transport (q z = v z q w ) of contaminants by increasing q w . However, also due to the plant transpiration, θ w will decrease, possibly causing the overall advection to decrease.…”
Section: Plant Effects On Physical/chemical Parametersmentioning
confidence: 99%